FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN INDEKS LQ45 DI BURSA EFEK INDONESIA - Nanang Ari Utomo (Faculty of Economic and Business Universitas STIKUBANK, 2016)
The company's value can be measured from the Price Book Value (PBV). PBV is the ratio of stock price to book value companies that show how much the stock price per share as compared to book value per share.The sample of this study consisted of 10 companies included in the index LQ45 firm and the index of Sembiring listed in Indonesia Stock Exchange during the years 2010 to 2013. Analytical techniques used are the Multiple Regression Analysis with a significance level α = 5%. Profitability positively effect and significantly on the value of the company. Company size negatively effect and significantly on the value of the company. Leverage positively effect and significantly on the value of the company. Corporate Social Responsibility positively effect and does not significantly on the value of the company. Keywords : Profitabilitas, Size company, Leverage and the value of the company.